Long-term Outcome of Selective Thoracic Fusion Using Rod Derotation and Direct Vertebral Rotation in the Treatment of Thoracic Adolescent Idiopathic Scoliosis: More Than 10-Year Follow-up Data. Issue 2 (March 2020) - Chang, Dong-Gune; Suk, Se-Il; Kim, Jin-Hyok; Song, Kwang-Sup; Suh, Seung-Woo; Kim, Soo-Yeon; Kim, Gang-Un; Yang, Jae Hyuk; Lee, Jung-Hee
Abstract : Study Design: This was a retrospective comparative study. Objective: To evaluate long-term outcomes of selective thoracic fusion (STF) using both rod derotation (RD) and direct vertebral rotation (DVR) with pedicle screw instrumentation (PSI) in the treatment of thoracic adolescent idiopathic scoliosis (AIS) with a minimum 10-year follow-up. Summary of Background Data: Postoperative compensation and maintenance of the unfused lumbar curve after STF is very important factor for the satisfactory results in the treatment of thoracic AIS. Patients and Methods: Sixty-five patients with thoracic AIS treated with STF from the neutral vertebra (NV) to NV or NV-1 with RD and DVR were retrospectively analyzed with a minimum 10-year follow-up. Patients were divided into 2 groups: satisfactory (n=52) and unsatisfactory groups (n=13). Unsatisfactory results were defined as an adding-on, a lowest instrumented vertebra (LIV) tilt of >10 degrees, or coronal balance >15 mm. Results: No significant differences were observed in the main thoracic curve between the satisfactory and unsatisfactory groups postoperatively ( P =0.218) and at the last follow-up ( P =0.636). Significant improvements of LIV tilt and disk angle were observed in both groups, but these improvements deteriorated during the follow-up period in the unsatisfactory group. Significant differences of apical vertebra (AV) and end vertebra (EV) were observed postoperatively (AV: P =0.001, EV: P =0.001) and at the last follow-up (AV: P <0.000, EV: P <0.000) between the 2 groups. Conclusions: STF using RD and DVR can achieve satisfactory deformity correction for thoracic AIS with satisfactory compensatory lumbar curve that was maintained over long-term follow-up. Progression of unfused lumbar curve closely related with LIV tilt and disk angle showing insufficient DVR. Therefore, STF with sufficient DVR required to achieve satisfactory deformity correction and prevent a distal adding-on phenomenon in the treatment of thoracic AIS.